2002
DOI: 10.1007/3-540-45876-x_5
|View full text |Cite
|
Sign up to set email alerts
|

Querying with Intrinsic Preferences

Abstract: Abstract. The handling of user preferences is becoming an increasingly important issue in present-day information systems. Among others, preferences are used for information filtering and extraction to reduce the volume of data presented to the user. They are also used to keep track of user profiles and formulate policies to improve and automate decision making. We propose a logical framework for formulating preferences and its embedding into relational query languages. The framework is simple, and entirely ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 18 publications
0
108
0
1
Order By: Relevance
“…However, the semantic meaning of these (user provided) combining functions is unclear and users often have to guess the 'right' weightings for their query. The area of operations research and research in the field of human preferences like [6] or [8] has already since long criticized this lack in expressiveness.…”
Section: Web Information Systems Architecture and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the semantic meaning of these (user provided) combining functions is unclear and users often have to guess the 'right' weightings for their query. The area of operations research and research in the field of human preferences like [6] or [8] has already since long criticized this lack in expressiveness.…”
Section: Web Information Systems Architecture and Related Workmentioning
confidence: 99%
“…The lack of expressiveness of this 'top k' query model, however, has first been addressed by [8] and with the growing incorporation of user preferences into database systems [6], [10] and information services [22] the limitations of the entire model became more and more obvious. This led towards the integration of so-called 'skyline queries' (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For the use in personalization in database retrieval and engineering of user preferences recent research in [7] and [13] has shown that these three operators (score aggregation, Pareto accumulation and lexicographic ordering) are the most common and essential constructors to build complex user preferences into queries allowing arbitrary combinations. Besides, also the closure of preference construction with these operators is shown for general partial orders.…”
Section: Utility-based Retrieval Modelsmentioning
confidence: 99%
“…For the same reasons we can safely output o 3 in K 2 after we have accessed o 6 . And after accessing o 7 we can output o 4 from K 1 (because it could only be dominated by o 2 in K 1 . However o 4 's score with respect to f 2 is strictly higher than o 2 's; thus it is not dominated by o 2 ).…”
Section: Observation 3: Correctness and Optimality For The Progressivmentioning
confidence: 99%
See 1 more Smart Citation